2004
DOI: 10.1074/jbc.m311703200
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2′-deoxycytidine Activates the p53/p21Waf1/Cip1 Pathway to Inhibit Cell Proliferation

Abstract: In addition to its demethylating function, 5-aza-2-deoxycytidine (5-aza-CdR) also plays an important role in inducing cell cycle arrest, differentiation, and cell death. However, the mechanism by which 5-aza-CdR induces antineoplastic activity is not clear. In this study, we found that 5-aza-CdR at limited concentrations (0.01-5 M) induces inhibition of cell proliferation as well as increased p53/p21Waf1/Cip1 expression in A549 cells (wild-type p53) but not in H1299 (p53-null) and H719 cells (p53 mutant). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
100
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 50 publications
19
100
0
2
Order By: Relevance
“…The inhibition of p21 WAF1/CIP1 upregulation by Pifithrin-a and the lack of p21 WAF1/CIP1 upregulation in the p53-null HL-60 cells support a major role of the DNA damage/p53 axis in this effect, which is consistent with the effect of DAC on human lung cancer cells (Zhu et al, 2004). Also, p21 WAF1/CIP1 upregulation in HCT116 cells in a DNMT1-and DNMT3b-independent manner further supports the hypothesis of DNA damage-induced upregulation of p21 WAF1/CIP1 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The inhibition of p21 WAF1/CIP1 upregulation by Pifithrin-a and the lack of p21 WAF1/CIP1 upregulation in the p53-null HL-60 cells support a major role of the DNA damage/p53 axis in this effect, which is consistent with the effect of DAC on human lung cancer cells (Zhu et al, 2004). Also, p21 WAF1/CIP1 upregulation in HCT116 cells in a DNMT1-and DNMT3b-independent manner further supports the hypothesis of DNA damage-induced upregulation of p21 WAF1/CIP1 .…”
Section: Discussionsupporting
confidence: 80%
“…DAC induced p21 WAF1/CIP1 expression in other systems. DAC induction of p21 WAF1/CIP1 expression in lung and colon cancer cells was p53 dependent and not associated with chromatin remodeling events (Karpf et al, 2001;Zhu et al, 2004). On the other hand, chromatin immunoprecipitation experiments suggested that treatment of KG-1 and KG-1a leukemia cells with DAC was associated with an increase in H3 acetylation at the unmethylated p21 WAF1/CIP1 promoter (Scott et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The tumour suppressor genes p16 INK4 and p53, which are critically involved in pancreatic cancer tumorigenesis, are also implicated in the response to 5-aza-CdR treatment (Bender et al, 1998;Suh et al, 2000;Nieto et al, 2004;Zhu et al, 2004). The analysis of the expression of p16 protein confirmed its upregulation after the treatment in both PaCa44 and CFPAC1.…”
Section: Discussionmentioning
confidence: 98%
“…5-AZA-dC and HDAC inhibitors can reactivate aberrantly hypermethylated or acetylated genes, thereby inhibiting tumor cells by inducing apoptosis, cell cycle arrest, and differentiation (32)(33)(34)(35). In addition to its demethylating function, 5-AZA-dC may also play an antineoplastic role that is methylation independent (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of cell viability by both 5-AZA-dC and HDAC inhibitors could also result from their genotoxic effects (10,15,37,41,42). 5-AZA-dC is incorporated into DNA and covalently binds with DNMTs with the 5-AZA-DNMT-DNA adducts causing DNA damage (43).…”
Section: Discussionmentioning
confidence: 99%